Persuasive Sentences In Digital Ads For New Student Admission At Politeknik Unggul LP3M Medan In Acadamic Year 2022/2023 - Hermansyah Hermansyah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The purpose of this study was to find out the selection strategy persuasive sentences used by Politeknik Unggul LP3M Medan to increase the interest of prospective students in academic year 2022/2023. This research applied a qualitative research type. Data collection techniques used by means of observation, collecting documents, interviews and engaging listening techniques. Data analysis techniques used by reducing data and validating data to get results that are in accordance with the formulation of the problem. Based on the results of the analysis, it can be concluded that persuasive sentences in digital ads on social media about Admission of New Students at Politeknik Unggul LP3M at academic year 2022/2023 contain elements of rationalization, elements of identification and elements of suggestion with the aim of influencing prospective new students.